Proceedings of the 4th International Symposium on Health Research (ISHR 2019) 2020
DOI: 10.2991/ahsr.k.200215.030
|View full text |Cite
|
Sign up to set email alerts
|

Stigma and Discrimination Against People Living with HIV and AIDS in Banyuwangi, East Java, Indonesia

Abstract: Banyuwangi occupies the third highest position for HIV cases in East Java. Stigma and discrimination is one of the challenges in the success of controlling HIV and AIDS. Stigma increases the prevalence of HIV and AIDS and stops social and medical support to the patients. The study aim to explore stigma and discrimination experienced by PLWHA in Banyuwangi. This was a qualitative study conducted in Blambangan regional hospital in 2016 through in-depth interviews to 19 informants who selected purposively and rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…This research states that respondents experienced physical stigmatization, such as isolation from doing handshakes, kissing their children, and feeding others. Suicidal ideation and discrimination of goods by families against PLHIV are also common discrimination (Made et al, 2020), which makes them separated from their families, such as using different cutlery and social distancing (Fauk, Hawke, Mwanri, & Ward, 2021). Some other studies also report that people do not want to use the same tools of work as PLHIV and are given warnings to stay away from neighbours (Njejimana & Hern, 2021), which may cause the loss of financial support from family (Quoc et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This research states that respondents experienced physical stigmatization, such as isolation from doing handshakes, kissing their children, and feeding others. Suicidal ideation and discrimination of goods by families against PLHIV are also common discrimination (Made et al, 2020), which makes them separated from their families, such as using different cutlery and social distancing (Fauk, Hawke, Mwanri, & Ward, 2021). Some other studies also report that people do not want to use the same tools of work as PLHIV and are given warnings to stay away from neighbours (Njejimana & Hern, 2021), which may cause the loss of financial support from family (Quoc et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Some other studies also report that people do not want to use the same tools of work as PLHIV and are given warnings to stay away from neighbours (Njejimana & Hern, 2021), which may cause the loss of financial support from family (Quoc et al, 2019). Verbal stigmatization, such as being reviled by family and neighbours to die immediately, discussed by neighbours regarding diseases (Njejimana & Hern, 2021), and revealing the HIV / AIDS status of PLHIV by health workers and families (Fauk et al 2021;Made et al, 2020). Generally, the public view HIV/ AIDS as a sin, so PLHIV deserve the stigma.…”
Section: Discussionmentioning
confidence: 99%
“…The forms of stigma and rejection that PLWHA receive in the family environment are in the form of ostracism and disposal of PLWHA to remote places, separation of cutlery at home, and divorce disputes from spouses (Al fatih dkk 2021). As a result of this, PLWHA experience anxiety, stress, and depression, which are indirectly related to the occurrence of significant changes in the quality of life, especially in the mental or psychological quality of PLWHA (Dewi et al, 2020;Murwani, 2020;Munthe et al, 2022). One study found that 31% of people living with HIV in Sub Saharan Africa had depressive symptoms, with 18% reporting symptoms of major depression.…”
Section: Msm (Malementioning
confidence: 99%
“…According to the existing state of knowledge, the majority of analyses presume that current HIV/AIDS patients suffer from serious mental issues marked by depression and anxiety ( 49 52 ). Social discrimination and isolation are significant contributors to psychological wellbeing issues among HIV-positive individuals ( 53 56 ).…”
Section: Literature Reviewmentioning
confidence: 99%